Import competition and firm productivity: Evidence from German manufacturing - Richard Bräuer; Matthias Mertens; Viktor Slavtchev (The World Economy, 2023)
We study how different types of import competition affect firm productivity using firm-product data from German manufacturing (2000–2014). Competition from high-income countries causes affected domestic firms to increase their productivity and lower their prices. Oppositely, import competition from low-wage countries does not lead to firm productivity gains. Instead, domestic firms' sales and input usage decline. Our findings confirm the intuition of ladder models that the effect of competition depends on the “closeness” of competitors. They are in line with widespread X-inefficiencies throughout the economy, which firms reduce in response to competition from high-income countries.
Keywords: 330; import competition; multi-product firms; productivity